Electrohydrodynamic forming of porous ceramic capsules from a preceramic polymer - Nangrejo, M; Bernardo, E; Colombo, P; Farook, U; Ahmad, Z; Stride, E; Edirisinghe, M (2009)
Porous polymeric near-spherical capsules, ~ 3.6 mm in diameter, were prepared using an electrodydrodynamic process. These capsules were pyrolysed to porous ceramics, ~ 3 mm in diameter. The ceramic capsules had interconnected pores of ~ 1.3 μm in size, and large cells with a mean size of 28 μm. The larger pores resemble the cells in a typical ceramic foam and were evenly distributed throughout the structure. A large proportion of the ceramic capsules contained 65-70% porosity, and their compressive strength was 0.2-0.4 MPa. © 2008 Elsevier B.V. All rights reserved.